Sea Urchin-Like MnO2/Biomass Carbon Composite Electrode Material for High-Performance Supercapacitors - Xiaoyu Zhao; Ning Wang; Lei Li; Zixun Fang; Shoufeng Tang; Jianmin Gu (Journal of Chemistry, 2024)
Manganese oxide materials for high-performance supercapacitors are as popular electrode materials of energy storage devices based on their high theoretical capacitance. However, its development is limited by its poor electrical conductivity and insufficient contact surface area, which causes the supercapacitor to fail to achieve its theoretical specific capacitance. In this paper, unique sea urchin-like MnO2/biomass carbon (BC) composite materials were prepared for supercapacitors, showing the lower resistance compared with pure MnO2, which possesses superior electrochemical performance due to the advances in outstanding electrical conductivity. The single electrode test results show that the composite material achieves a specific capacitance of 205.5 F·g−1 at the current density of 0.5 A·g−1; with the current density increasing by a factor of 20, the supercapacitor loaded with this composite still retained 63.2% of its initial capacitance, showing its high rate performance. Meanwhile, the constructed asymmetric supercapacitor can change the color of electrochromic devices and drive the light of electrochemiluminescent devices, indicating its promising application. This work provided a promising route for the rational construction of multiple dimensioned high-performance electrode materials for use in new energy storage devices.